The study of schizogenous formation of secretory ducts in Ferula ferulaeoides (Steud.) Korov. - Liu, Meng-meng; Zhao, Yuan-yuan; Ma, Ying; Liu, Shuang-shuang; Yao, Jia-qi; Chi, Ya-ping; Li, Hui-fang; Liao, Kai; Zhu, Yun (Protoplasma, 2022)
The secretory ducts of Ferula ferulaeoides (Steud.) Korov. are the main tissue of synthesis, secretion, and accumulation of resin. The formation of secretory ducts is closely related to the harvest and quality of resin, but the lumen formation mode and corresponding mechanism have not been thoroughly studied. This study of F. ferulaeoides investigated the microstructure and ultrastructure of the secretory ducts from a developmental point of view. Stem samples were analyzed by light microscopy, transmission electron microscopy, and fluorescence microscopy. The data results showed (1) the walls of secretory cells were intact during the development of secretory ducts in F. ferulaeoides; (2) the plastids and endoplasmic reticulum of secretory cells participated in the synthesis of resin; (3) pectinase was involved in the degradation of the middle lamella; and (4) no features of programmed cell death during the formation of secretory ducts. The results suggested that the formation of F. ferulaeoides' secretory ducts was schizogenous, and pectinase was involved in its formation. These data may be beneficial to further explore the formation of secretory duct in other species of Ferula L. and the formation mechanism of schizogenous secretory structures.